Cenários biofísicos e ordenamento territorial no litoral sul de Sergipe - Oliveira, Anízia Conceição de Assunção (2013)
Scenarios are tools of analysis for understanding the evolution of the landscape from the interpretation of the directions and speeds of transformations in space. Because they allow for reflection on the consequences of forms of use and occupation of the territory, are adopted as useful tools to spatial planning, since they contribute to the orientation of current and future uses compatible with the control of human pressures and proposals for actions that do not compromise the biophysics integrity. Considering the issues related to the current pattern of use and occupation of the coastal zone and based on the search for understanding of the pressures, levels of degradation and the state of the environment, this study aimed at the development of biophysical scenarios for The Coastal Plains of municipalities Estancia and Itaporanga D'Ajuda-SE, aiming, from the perspective of an integrated analysis of the landscape, the proposition of the priority actions (Scenario Recommended) compatible with the sensitivity of natural environments, and the analysis of the possibilities of events triggered from the achievement or not this proposal (Exploratory Scenarios) as subsidy to territorial planning. The development of the scenarios in this research was made possible primarily by the delineation and classification of units of landscapes based on parameters related to the morphology, to the lithology, to the allies aspects the vegetation cover and land use, which allowed the identification of the occupancy levels each compartment and, second, the analysis of the environmental state of the landscape. The subdivision of the Coastal Plains of Estancia and Itaporanga D'Ajuda in units of landscape and the analysis of the environmental state of each compartment, by considering the ecological components and spatial discontinuities resulting from anthropogenic interferences, allowed a better understanding of current configuration of the landscape in terms of elements and processes involved, as well as of the existence of certain specificities concerning to the limits and potential of each unit